2019
DOI: 10.1101/604538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR/Cas9 Treatment Causes Extended TP53-Dependent Cell Cycle Arrest In Human Cells

Abstract: While the mechanism of CRISPR/Cas9 cleavage is understood, the large variation in mutant recovery for a given target sequence between cell lines is much less clear. We hypothesized that this variation may be due to differences in how the DNA damage response affects cell cycle progression. We used incorporation of EdU as a marker of cell cycle progression to analyze the response of several human cell lines to CRISPR/Cas9 treatment with a single guide directed to a unique locus. Cell lines with functionally wild… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Since CNA occur frequently in solid tumors, we may be underestimating the number of associations in these cancer types. Second, alternative dependency scores could be used as input to SuperDendrix; recent studies have demonstrated that CERES scores can be affected by other covariates and confounding variables [93,94]. Third, we found that some differential dependencies are associated with multiple sets of features (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…Since CNA occur frequently in solid tumors, we may be underestimating the number of associations in these cancer types. Second, alternative dependency scores could be used as input to SuperDendrix; recent studies have demonstrated that CERES scores can be affected by other covariates and confounding variables [93,94]. Third, we found that some differential dependencies are associated with multiple sets of features (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…In a co‐submitted manuscript, Ihry et al () reported similar findings in another cell line. These results have since been independently reproduced by several groups using RPE‐1 cells and other normal human cell types (Li et al , ; Cullot et al , ; preprint: Geisinger & Stearns, ; Schiroli et al , ; preprint: van den Berg et al , ). The significant attention that our work received was due to the relevance of our conclusions for genome editing in normal human cells and for the development of cell‐based therapies.…”
mentioning
confidence: 67%
“…The RPE1‐Cas9 cells Brown et al use seem to heavily overexpress Cas9 (Zimmermann et al , ). This is expected to lead to very fast kinetics of DNA cutting, and more persistent binding of Cas9 to its target site after the cut (preprint: Geisinger & Stearns, ). Thus, the very high Cas9 expression in their cells (Zimmermann et al , ) is a plausible explanation for why both screens detected the positive selection for loss of p53, but only our screens clearly distinguished between the drop‐out performance of p53 wild‐type and p53 null cells.…”
mentioning
confidence: 99%
“…Additionally, several recent studies have indicated increased genome editing efficiencies in cells with reduced activation of the P53 pathway [99]. Moreover, increased activation of this pathway is associated with prolonged nuclease activity [100]. While this indicates that genome editing triggers cell cycle arrest and apoptosis [99,100], it could further suggest that surviving, proliferating genome-edited cells might display pro-tumorigenic capabilities.…”
Section: Future Prospects Of Gene Editing In Genodermatosesmentioning
confidence: 99%
“…Moreover, increased activation of this pathway is associated with prolonged nuclease activity [100]. While this indicates that genome editing triggers cell cycle arrest and apoptosis [99,100], it could further suggest that surviving, proliferating genome-edited cells might display pro-tumorigenic capabilities. Other recent studies have described frequent large on-target deletions [73,101] and P53-dependant chromosomal translocations associated with genome editing [102].…”
Section: Future Prospects Of Gene Editing In Genodermatosesmentioning
confidence: 99%